BOOK REVIEW: THE TRAPPED TUNISIAN SOCIETY’S IN CULTURAL ALIENATION: LANGUAGE HANDICAP AND TROUBLED IDENTITY - BERRACHED, MOHAMED (Society Register, 2018)
The author’s longitudinal study of the issue of languages has led him to find out that normal relationships, which people usually have with their own languages require four necessary conditions: 1- They must speak to each other only in their own languages 2- They must use them in writing 3- They must have good knowledge of the meanings of the words of their languages as well as of their grammatical and spelling rules. 4- The full practice of 1,2 and 3 by the citizens and the institutions in societies leads to intimate relationships with the languages: love the languages, defend them and be proud of them.